Analyzing Sustainable Practices in Fashion Supply Chain - Sheetal Soni; Sejal Baldawa (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2023)
Fast fashion brands create high quantities of synthetic, petroleum-based garments that result in high levels of textile waste and emissions. To change the dreadful tag of hazardous production, top-notch fast fashion leaders started paying attention towards adopting sustainable practices, including sustainable supply chain management (SSCM).This paper conducts a structured review of the annual reports on the topic of energy efficiency and environmental sustainability practices adopted by fashion brands in the supply chain management context. This study tries to identify the factors and classification influencing energy efficiency and environmental sustainability initiatives that impact supply chain performance, the customer perspective and the different technologies supporting energy efficiency and sustainable practices based on the analysis of the data related to the sustainability of top fashion brands from their past five year annual reports.